The asymmetric effects of tariffs on intra-firm trade and offshoring decisions - Federico J. Díez (Federal Reserve Bank of Boston, 2010)
This paper studies the effects of tariffs on intra-firm trade. Building on the Antràs and Helpman (2004) North-South theoretical framework, I show that higher Northern tariffs reduce the incentives for outsourcing and offshoring, while higher Southern tariffs have the opposite effects. I also show that increased offshoring and outsourcing imply an increase in the ratio of Northern intra-firm imports to total imports, which is an empirically testable prediction. Using a highly disaggregated dataset of U.S. (the North) imports and relevant tariffs, I find robust evidence to support the models predictions.
Keywords: F10; F23; L22; L23; 330; Intra-firm trade; offshoring; outsourcing tariffs; Zoll; Außenhandelsbeschränkung; Intraindustrieller Handel; Offshoring; Outsourcing; Nord-Süd-Beziehungen; Theorie; USA; Welt